The first report of cases of pet dogs with naturally occurring cancer treated with the antitumor peptide CIGB-552. (October 2017) - Vallespi, Maribel G.; Rodriguez, Juan C.; Seoane, Lilibet Calaña; Alvarez, Patricia; Santana, Hector; Garay, Hilda; Cabrera, Ibrahim Acosta; Espinosa, Joan Torres; Reyes, Osvaldo
Abstract: The absence of an effective therapy against human solid tumors has fostered the development of promising antineoplastic therapeutic candidates, as the CIGB-552 peptide. This synthetic peptide has shown to be effective in reducing tumor size and increasing the lifespan in tumor-bearing mice. Therefore, this work was aimed to explore the safety profile and preliminary assessment of antitumor activity of the CIGB-552 peptide therapeutic candidate in a small population of dogs (n = 9) having malignant spontaneously-arising solid tumors. The peptide was administered by subcutaneous (s.c.) route, at three dosage levels (0.075, 0.15 and 0.3 mg/kg). The results showed no dose-limiting toxicities in any dogs. The antitumor activity observed in dogs receiving CIGB-552 was associated with the reduction in the tumor volume. Given the antitumor effects of CIGB-552 as mediated by COMMD1 protein, which function is highly conserved among eukaryotic organisms, and the similarities of canine and human types of cancer with respect to tumor biology, it is likely that CIGB-552 could demonstrate comparable anti-cancer activity in human patients. Synthetic peptide, COMMD1, Tumor, Dog, CIGB-552. Highlights: First study with the anticancer peptide CIGB-552 in a model of spontaneous tumor in dog The antitumor peptide CIGB-552 was safe and well tolerate in dogs with naturally occurring cancer. Subcutaneous administration of CIGB-552 showed objective response in dogs with measurable tumors. Studies in tumor-bearing dogs are useful to validate the protein COMMD1 as a novel target for cancer treatment.